Exposure to dim light at night alters daily rhythms of glucose and lipid metabolism in rats - Rumanova, Valentina Sophia; Okuliarova, Monika; Foppen, Ewout; Kalsbeek, Andries; Zeman, Michal (Frontiers in Physiology, 2022)
Nocturnal light pollution has been rapidly increasing during the last decades and even though dim artificial light at night (ALAN) has been associated with metabolic diseases, its mechanism is still far from clear. Therefore, the aim of our study was to thoroughly analyze the effects of ALAN on energy metabolism, metabolites, metabolic hormones, and gene expression. Male Wistar rats were kept in either the standard light:dark (12:12) cycle or exposed to ALAN (~ 2 lx) during the whole 12-hour dark phase for 2 weeks. Energy metabolism was measured in metabolic cages. In addition, we measured plasma and hepatic metabolites, clock and metabolic gene expression in the liver and epididymal adipose tissue, and plasma hormone levels. In ALAN rats, we observed an unexpected transitory daytime peak of locomotor activity and a suppression of the peak in locomotor activity at the beginning of the dark period. These changes were mirrored in the respiratory exchange ratio. Plasma metabolites became arrhythmic, and plasma and hepatic cholesterol levels were increased. Lost rhythmicity of metabolites was associated with disrupted behavioral rhythms and expression of metabolic genes. In the liver, the rhythms of metabolic sensors were either phase-advanced (Ppara, Pgc1a, Nampt) or arrhythmic (Sirt1, Lxra) after ALAN. The rhythmic pattern of Ppara and Sirt1 was abolished in the adipose tissue. In the liver, the amplitude of the daily rhythm in glycogen content was attenuated, the Glut2 rhythm was phase-advanced and Foxo1 lost its daily rhythmicity. Moreover, hepatic Foxo1 and Gck were up-regulated after ALAN. Interestingly, several parameters of lipid metabolism gained rhythmicity (adiponectin, Hmgcs2, Lpl, Srebf1c) in the liver, whereas Noct became arrhythmic in the adipose tissue. Peripheral clock genes maintained their robust oscillations with small shifts in their acrophases. Our data show that even a low level of ALAN can induce changes in the daily pattern of behavior and energy metabolism, and disturb daily rhythms of genes encoding key metabolic sensors and components of metabolic pathways in the liver and adipose tissue. Disturbed metabolic rhythms by ALAN could represent a serious risk factor for the development and progression of metabolic diseases.